US-Chinese relations and the most prominent controversial issues - Sabah Saber, Lecturer Dr. Ali (The college of law and political science journal, 2023)
The end of the Cold War is an important turning point in the course of internationalUHODWLRQVHVSHFLDOO\WKHJUHDWSRZHUVWKDWKDYHLQÁXHQFHLQLQWHUQDWLRQDOUHODWLRQVas the collapse of the (former) Soviet Union represented a strategic opportunityfor American hegemony and leadership over the world at all levels, whether at thepolitical, military or economic levels. The United States did this, but it tried to spreadAmerican culture in all its dimensions on the world level, as it provides an ideallife, and this contradicts the thought of many countries, whether they are allies oropponents of the United States of America , Therefore, the end of the Cold War isconsidered the beginning of work to get out of the American mantle of countrieswith different political, social and economic backgrounds. The best example of thisLV&KLQDZKHUHWKHQLQHWLHVRIWKHODVWFHQWXU\UHSUHVHQWHGWKHEHJLQQLQJRIFRQÁLFWand competition by the Chinese dragon against the dominant in the internationalarena (United States of America)